Teaching Visual Texts with Multimodal Analysis Software - Lim Fei, V.; O'Halloran, Kay; Tan, S.; E, M. (Springer, 2015)
This exploratory study introduces the systemic approach and the explicit teaching of a meta-language to provide conceptual tools for students for the analysis and interpretation of multimodal texts. Equipping students with a set of specialised vocabulary with conventionalised meanings associated with specific choices in multimodal texts empowers them to support their interpretations with reference to textual evidence. The aim of the current study is to explore the extent to which the systemic approach may be supported by multimodal analysis software, in this case for the study of print advertisements in Singapore’s secondary schools. A mixed method approach is used to derive the findings from this study. Instruments used include lesson observations and interviews with teachers and students, as well as user-experience surveys. Findings from the study indicate that there is value in the systemic approach to teaching visual texts, and that it can be usefully supported by multimodal analysis software as an annotation and analytical tool. This is subject to further customisation of the learning packages, more in-depth professional development for teachers, and improvements to the technical functionalities in the software. The designed affordances for multimodal analysis software derived from the study, which have been implemented in the new version of the software, are discussed.